(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Middle Eastern writer, Nawal El Saadawi explores the unpleasant experience of women in the male dominated Egyptian society.Saadawi’s Woman at Point Zero exposes the oppression and emancipation of women from the patriarchal social milieu. The paper focuses the resilient and revolutionist attitude of the protagonist Firdaus in her strives towards claiming freedom from the clutches of the society.